Synthesis And Characterization Of Manganese Dioxide Nanoparticles Via Direct Heating Method - Wong, Chee Leong (Universiti Sains Malaysia, 2018)
Coloured effluent discharged from textile industry has become critical environmental concern since it is difficult to be degraded. Advanced oxidation process (AOPs) using photocatalyst is one of the emerging techniques for effluent treatment, but most of the wide-bandgap photocatalyst is Ultraviolet (UV)-activated which is not practical in thereal environment. Also, problem arises when there is a need to remove these photocatalyst in particle form from the treated effluent after application. In this project, narrow-bandgap MnO2 nanoparticles were synthesized using co-precipitation and sol gel methods. MnO2 nanoparticles were also grown on the Khantal wire coil via direct heating synthesis. The resulting products were characterised using various analytical tools (e.g. X-Ray Diffraction (XRD), X-Ray photoelectron spectroscopy (XPS), Scanning Electron Microscopy (SEM), Transmission Electron Microscope (TEM)) and were employed for dye removal study under UV, visible light irradiation and dark condition with addition of hydrochloric acid (HCl) or sulphuric acid (H2SO4). MnO2 nanoparticles alone was not efficient in removing dye. With addition of H2SO4, removal efficiency reached 96.63% and 57.93% after 12min for nanoparticles synthesized by co-precipitation and sol gel methods respectively. Washing of nanoparticles with deionised water and ethanol inluenced the dye removal efficiency. It was found that the removal mechanism of MnO2 nanoparticles was oxidative degradation process. To minimise lost of nanoparticles, MnO2 nanoparticles with hierarchical structures were grown on the wire coil with various heating power and growth time. Secondary nucleation was prominent with increasing heating power whereas Ostwald ripening was obvious with increasing growth time. Besides, MnO2 nanoparticles grown on wire coil could be used for dye removal process. MnO2 nanoparticles grown with heating power of 30W with 10min growth time and growth duration of 30min at 24W exhibited highest efficiency which were 98.25% and 85.69%, respectively.